Enterprise and Organizational Modeling and Simulation 11th International Workshop, EOMAS 2015, Held at CAiSE 2015, Stockholm, Sweden, June 8-9, 2015, Selected Papers - Barjis, Joseph; Pergl, Robert; Babkin, Eduard (Lecture Notes in Business Information Processing, 2015)
This book constitutes the refereed proceedings of the 11th International Workshop on Enterprise and Organizational Modeling and Simulation, EOMAS 2015, held at CAiSE 2015, in June 2015 in Stockholm, Sweden. EOMAS was founded with the purpose to become a forum among researchers and practitioners to share their research and practical findings by encouraging the dissemination of research results under a more generic umbrella called enterprise engineering, which encompasses internal factors ranging from organizational complexity to intricacy of business processes and sophistication in workflows as well as external factors and uncertainties such as competition, politics, or the emergence of innovative technologies. The 15 papers presented in this volume were carefully reviewed and selected from 28 submissions. They were organized in topical sections named: enterprise conceptual modeling and simulation; enterprise modeling formal foundation; and enterprise optimization.